Health utility decreases with increasing clinical stage in amyotrophic lateral sclerosis. Issue 3 (1st June 2014) - Jones, Ashley R.; Jivraj, Naheed; Balendra, Rubika; Murphy, Caroline; Kelly, Joanna; Thornhill, Marie; Young, Carolyn; Shaw, Pamela J.; Leigh, P. Nigel; Turner, Martin R.; Steen, I Nick; McCrone, Paul; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease typically causing death within three years. Understanding the impact of disease on patients using health utility at different stages of ALS would allow meaningful cost-benefit analysis of new potential therapies. A common health-related quality of life measurement, developed and validated for the UK, is the EQ-5D. Using clinical trial data from the LiCALS study, we calculated health utility using the EQ-5D for each King's ALS clinical stage from 214 patients. We analysed whether health utility, and other health-related measures, significantly changed between each of the clinical stages. Results showed that mean health utility decreased by 0.487 (the scale runs from 1 to – 0.594) between clinical stages 2A and 4. Emotional states, measured using the Hospital Anxiety and Depression Scale (HADS), showed worsening depression and anxiety scores as ALS progressed. Age of onset, disease onset, gender and treatment group were not predictors of EQ-5D, depression or anxiety. In conclusion, increasing severity of King's ALS Clinical Stage is associated with a progressive decrease in EQ-5D health utility. This is useful for cost-benefit analysis of new therapies and validates this ALS clinical staging system.